2023
DOI: 10.2355/isijinternational.isijint-2022-348
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization Characteristics of Iron Ore Sinter and the Effects of Cooling Rate on Mineral Phase Structure

Abstract: The mineral phase composition and structure of sintered ore are closely related to its quality. Analyzing the characteristics of the phase structure of sintered ores and studying the influence of sintering conditions are important to optimize their quality. In this study, the mineralization characteristics of ore during the sintering process were studied through interrupted quenching experiments. The results clarified the evolution of the structure of the sintered ore phases during the heating and cooling and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Other work has described the morphology of magnetite crystals changing from idiomorphic when part of a phase assemblage consisting of magnetite + liquid only at 623 K, to irregular shapes after cooling to room temperature, indicating that the formation of SFCA phases consumed magnetite during the cooling process and with the crystal structures of the SFCA phases containing spinel structural modules. 28) Nicol et al also reported the formation of phase(s) with SFCA-I structure forming during cooling of an Al 2 O 3 composition (i.e., in the SFC system) from a liquid phase at 1623 K. 29,30) The evidence, therefore, that the formation of SFCA-I after melt formation and during cooling does occur is becoming overwhelming, and logically this appears consistent with SFCA-I being intermediate between SFCA-III and SFCA in terms of ordering of the spinel (S) and pyroxene (P) structural modules.…”
Section: Figures 1a To Cmentioning
confidence: 99%
“…Other work has described the morphology of magnetite crystals changing from idiomorphic when part of a phase assemblage consisting of magnetite + liquid only at 623 K, to irregular shapes after cooling to room temperature, indicating that the formation of SFCA phases consumed magnetite during the cooling process and with the crystal structures of the SFCA phases containing spinel structural modules. 28) Nicol et al also reported the formation of phase(s) with SFCA-I structure forming during cooling of an Al 2 O 3 composition (i.e., in the SFC system) from a liquid phase at 1623 K. 29,30) The evidence, therefore, that the formation of SFCA-I after melt formation and during cooling does occur is becoming overwhelming, and logically this appears consistent with SFCA-I being intermediate between SFCA-III and SFCA in terms of ordering of the spinel (S) and pyroxene (P) structural modules.…”
Section: Figures 1a To Cmentioning
confidence: 99%